Experimental study of the thermal characteristics of microencapsulated phase change composite cylinders. (5th March 2017) - Fang, Y.; Qu, Z.G.; Fu, Y.D.
Abstract: The melting thermal performance of hollow cylinder microencapsulated phase change material (MEPCM) composite samples is investigated for thermal energy storage applications. Temperatures at different radial positions and the growth of liquid–solid interfaces in the samples are analyzed under the influence of the MEPCM particle fraction, the PCM core fraction in the particles, and the mass fraction of additives with high thermal conductivity. The liquid–solid interface increases at constant speeds for different samples. The higher the fraction of MEPCM particles in a sample, the more time the phase change process consumes, thereby revealing that more energy is converted to latent heat for PCM. There is a mild difference in the duration of the phase change process in samples with different PCM core fractions. At a similar phase change duration, the average temperature is lower in the samples with a higher core fraction. The effect of the additives is related to micromorphology. When additives are added to the samples, the temperature distribution is more uniform, and the duration of the phase change process is shorter due to the enhanced thermal diffusivity.